The Influence Of Social Media, Price, And Service Quality On The Decision To Choose Hafiz Rakhmatullah Dentist Clinic In Banjarmasin City - Faryska Nur Ichsanudin*; Muhammad Bukhori; Widi Dewi Ruspitasari (Riwayat: Educational Journal of History and Humanities, 2023)
Increasing public awareness of dental and oral health is followed by an increase in the number of dentist clinics in the city of Banjarmasin. The aims of this research are to determine and analyze (1) the influence of social media on the decision to choose a dentist clinic, (2) the influence of price on the decision to choose a dentist clinic, (3) the influence of service quality on the decision to choose a dentist clinic (4) The simultaneous influence of social media, price and service quality on the decision to choose a dentist clinic. This research used a quantitative descriptive approach to patients who visited dentist Hafiz Rakhatullah's clinic in Banjarmasin City. The research population was patients who had visited at least once in May to June 2023 with a research sample of 100 respondents using accidental sampling techniques. The analysis technique uses the SPSS version 27 program. The test instruments used are validity test, classical assumption test, multiple linear regression analysis, hypothesis test, coefficient of determination test, and dominance test. The results show (1) social media influences purchasing decisions, (2) price influences purchasing decisions, (3) service quality influences purchasing decisions, and (4) simultaneously social media, price, and service quality influence purchasing decisions.